Characterization of the crack initiation and propagation in Alloy 600 with a cold-worked surface. (15th May 2019) - Shen, Zhao; Chen, Kai; Tweddle, David; He, Guanze; Arioka, Koji; Lozano-Perez, Sergio
Highlights: Crack initiation and propagation in Alloy 600 with a cold-worked surface were investigated. Mechanical polishing introduced a layer of nanograins and the nanograin boundaries were preferentially oxidized. Intergranular oxidation and crack growth in the deformation layer terminated at the deformation layer-matrix interface. Intergranular oxidation and discrete oxide particles were observed ahead of crack tips, suggesting an intergranular selective oxidation mechanism. A new understanding of SCC initiation and propagation in Alloy 600 with a cold-worked surface was developed. Abstract: The crack initiation on a cold-worked surface of Alloy 600, exposed to simulated pressurized water reactor primary water, was mechanistically studied through high-resolution characterization. Mechanical polishing introduced a thin recrystallization layer on the specimen surface, which lead to the crack initiation along highly-deformed recrystallization grain boundaries after preferential oxidation. Intergranular crack propagation occurred once the initiation cracks met the matrix grain boundaries under the external loading and the residual stress introduced by the prior 20% cold working. The controlling mechanism of SCC crack propagation was believed to be an intergranular selective oxidation mechanism.